THE INFLUENCE OF GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILITY AND PROFITABILITY ON FIRM VALUE - Dahlia, Ake; Hadiwibowo, Imam; Azis, Mohammad Taufik (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: This study aims to determine the effect of green accounting, corporate social responsibility and profitability on firm value. Methods: This research uses a quantitative method with a descriptive approach, with a research sample of 18 energy sector companies listed on the Indonesia Stock Exchange between 2021-2023. The data used is secondary data. This research uses Eviews 8 software to test panel data regression. Results: The results showed that green accounting and CSR have no effect on firm value. However, profitability has a significant effect on firm value, which shows that higher profitability will increase shareholder wealth and company valuation. Conclusion and suggestion: This study concludes that although profitability plays an important role in determining firm value, currently green accounting and CSR disclosure have no significant effect on firm value due to data limitations and investor priorities. Future research should be expanded to include additional factors, such as environmental performance and investment decisions, and increase the sample size for broader generalization. Companies are advised to increase transparency and standardization in environmental reporting to build stakeholder trust and strengthen their market position.